URGENSI RECHTERLIJK PARDON DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Hunowu, Bella Putri; Puluhulawa, Fenty U.; Dungga, Weny Almoravid (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This research discusses changes in Indonesian criminal law regarding legal forgiveness, as one type of decision in criminal cases. The journal aims to understand the urgency and purpose of studying the values of Pancasila that underlie the regulations and implementation of legal forgiveness. The research uses a normative juridical approach with a legislative and conceptual approach. The journal finds that judicial forgiveness is a manifestation of Pancasila values in the process of enforcing criminal law and is part of an effort to Indonesianize those regulations. Criminal law, which has hitherto been based on principles of colonial states.